LAND OWNERSHIP BASED ON NATIONAL LAND LAW IN INDONESIA - Irene Eka Sihombing (Warmadewa Press, 2018)
This study examines the certainty of ownership of land rights under the national law on land in Indonesia. It is a type of nomative focusing on reviewing the laws governing land and ownership for Indonesian citizens and foreign nationals living in Indonesia. The approaches used were the conceptual and statute approaches to legislation. The data collected are in the form of articles of law that regulate and related to land and ownership. Qualitative method was a method used in analyzing and presenting data. The results indicate that the statutory provisions are indispensable. The ownership of land rights previously adopted from the Land Law of the West is no longer applicable to date in Indonesia. The study is recommended for those interested in the system and land law investigations to be used as reference material in the theoretical and practical review of the law.